How homologous recombination maintains telomere integrity - Tacconi, E; Tarsounas, M (Springer Berlin Heidelberg, 2015)
Telomeres protect the ends of linear chromosomes against loss of genetic information and inappropriate processing as damaged DNA and are therefore crucial to the maintenance of chromosome integrity. In addition to providing a pathway for genome-wide DNA repair, homologous recombination (HR) plays a key role in telomere replication and capping. Consistent with this, the genomic instability characteristic of HR-deficient cells and tumours is driven in part by telomere dysfunction. Here, we discuss the mechanisms by which HR modulates the response to intrinsic cellular challenges that arise during telomere replication, as well as its impact on the assembly of telomere protective structures. How normal and tumour cells differ in their ability to maintain telomeres is deeply relevant to the search for treatments that would selectively eliminate cells whose capacity for HR-mediated repair has been compromised.